Glycan recognition by collectin-11 drives SARS-CoV-2 infectivity and membrane injury of respiratory epithelial cells - Anastasia Polycarpou; Tara Wagner-Gamble; Roseanna Greenlaw; Lauren O’Neill; Varsha Kanabar; Alanoud Alrehaili; Yusun Jeon; Jonathan Baker; Mona Bafadhel; Hataf Khan; Michael H. Malim; Marco Romano; et al. (Proceedings of the National Academy of Sciences, 2025)
SARS-CoV-2 respiratory-tract infection affects both vaccinated and unvaccinated persons suggesting factors besides adaptive immunity are operative. We investigated the role of collectin-11 (CL-11), an epithelial-secreted carbohydrate-binding lectin that drives innate immunity and eliminates pathogens by complement activation. SARS-CoV-2, despite binding CL-11 to activate complement, was resistant to lysis. Remarkably, opsonization by CL-11 enhanced virus production by infected respiratory epithelial cells independently of complement. Furthermore, infected cells expressing SARS-CoV-2 spike protein displayed enhanced vulnerability to CL-11 binding and membrane attack by complement. The mechanism of enhanced infectivity was ablated in the presence of L-fucose, which occupied the extended carbohydrate-binding cleft of CL-11 in a crystallographic analysis of complexes between L-fucose and CL-11. Our study suggests pathogenicity of SARS-CoV-2 is related to complement-resistance together with enhanced infectivity and injury of respiratory epithelial cells mediated by locally released CL-11.